Exploring Students’ Reading Comprehension through Cooperative Learning-based Digital Interactive Media - Aghisni; Widia Nur Jannah; Dewi Yulianawati (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores students’ reading comprehension before and after implementing a cooperative learning model supported by digital interactive media. Conducted at SDN 1 Jamblang with 35 third-grade students, the research applied a one-group pretest-posttest design. The Student Teams Achievement Division (STAD) model was integrated with interactive media such as images, videos, and quizzes, adjusted to the school’s limited technology. Data were collected through reading comprehension tests, observations, and documentation. The average pretest score was 59.14, rising to 82.60 in the posttest, with a normalized gain score of 0.6094 (moderate improvement). Observational results showed strong engagement, with teacher implementation at 81.25% and student activity at 90.63%. These findings indicate that cooperative learning, when enhanced with digital interactive tools, can effectively improve students’ reading comprehension. Theoretically, this study supports Vygotsky’s and Piaget’s views by demonstrating how digital media and cooperative learning promote cognitive growth through social interaction and developmentally appropriate strategies. Practically, it offers a replicable model for educators aiming to improve literacy, especially in technology-limited schools. This approach offers a promising alternative for enhancing reading instruction and deserves further development to support digital-era literacy learning.